The treatment efficacy of bone tissue engineering strategy for repairing segmental bone defects under diabetic condition - Wang, Xiangsheng; Xiang, Can; Huang, Chunhua; Cheng, Hanxiao; Zhou, Zhentao; Zhang, Jufang; Xie, Hui (Frontiers in Bioengineering and Biotechnology, 2024)
Background: Diabetes mellitus is a systematic disease which exert detrimental effect on bone tissue. The repair and reconstruction of bone defects in diabetic patients still remain a major clinical challenge. This study aims to investigate the potential of bone tissue engineering approach to improve bone regeneration under diabetic condition. Methods: In the present study, decalcified bone matrix (DBM) scaffolds were seeded with allogenic fetal bone marrow-derived mesenchymal stem cells (BMSCs) and cultured in osteogenic induction medium to fabricate BMSC/DBM constructs. Then the BMSC/DBM constructs were implanted in both subcutaneous pouches and large femoral bone defects in diabetic (BMSC/DBM in DM group) and non-diabetic rats (BMSC/DBM in non-DM group), cell-free DBM scaffolds were implanted in diabetic rats to serve as the control group (DBM in DM group). X-ray, micro-CT and histological analyses were carried out to evaluate the bone regenerative potential of BMSC/DBM constructs under diabetic condition. Results: In the rat subcutaneous implantation model, quantitative micro-CT analysis demonstrated that BMSC/DBM in DM group showed impaired bone regeneration activity compared with the BMSC/DBM in non-DM group (bone volume: 46 ± 4.4 mm3 vs. 58.9 ± 7.15 mm3, *p<0.05). In the rat femoral defect model, X-ray examination demonstrated that bone union was delayed in BMSC/DBM in DM group compared with BMSC/DBM in non-DM group. However, quantitative micro-CT analysis showed that after 6 months of implantation, there was no significant difference in bone volume and bone density between the BMSC/DBM in DM group (199 ± 63 mm3 and 593 ± 65 mg HA/ccm) and the BMSC/DBM in non-DM group (211 ± 39 mm3 and 608 ± 53 mg HA/ccm). Our data suggested that BMSC/DBM constructs could repair large bone defects in diabetic rats, but with delayed healing process compared with non-diabetic rats. Conclusions: Our study suggest that biomaterial sacffolds seeded with allogenic fetal BMSCs represent a promising strategy to induce and improve bone regeneration under diabetic condition.